Is Nematocharax (Actinopterygii, Characiformes) a monotypic fish genus? - Barreto, Silvia Britto; Nunes, Lorena Andrade; Silva, Andre Teixeira da [UNESP]; Juca-Chagas, Ricardo; Diniz, Debora; Sampaio, Iracilda; Schneider, Horacio; Antunes de Mello Affonso, Paulo Roberto (Canadian Science Publishing, Nrc Research Press, 2016)
The combination of DNA barcodes and geometric morphometrics is useful to discriminate taxonomically controversial species, providing more precise estimates of biodiversity. Therefore, our goal was to assess the genetic and morphometric diversity in Nematocharax, a controversial monotypic and sexually dimorphic genus of Neotropical fish, based on sequencing of cytochrome c oxidase subunit I (COI) and morphometric analyses in seven populations of N. venustus from coastal rivers in Brazil. The average pairwise intrapopulation divergence in COI ranged from 0 to 2.2%, while the average pairwise interpopulation divergence varied from 0 to 7.5%. The neighbour-joining (NJ) tree resulted in five genetic groups (bootstrap >= 97%), which correspond to the five clusters delimited by the BIN System, GMYC, and bPTP, indicating that there might be at least five species (or OTUs) within Nematocharax. Morphometric differences among these genetic lineages were also identified. Apparently, sexual selection, restricted dispersal, and geographic isolation might have acted synergistically to cause the evolutionary split of populations. These data challenge the current view that Nematocharax is a monotypic genus inasmuch as evolutionarily significant units or even distinguished species were identified. Therefore, we recommend that the highly impacted coastal basins in northeastern Brazil should be prioritized in conservation plans.
Keywords: COI; DNA barcoding; ichthyofauna; geometric morphometrics; species delimitation